Engaging imagination and developing creativity in education - Egan, Kieran; Juddon, Gillian; Madej, Krystina (Cambridge Scholars Publishing, 2015)
Imagination is the source of creativity and invention. This volume of essays has been collected expressly to bring readers new ideas about imagination and creativity in education that will both stimulate discussion and debate, and also contribute practical ideas for how to infuse daily classrooms with imaginative activities. Researchers and educators around the world have taken up the discussion about the importance of imagination and creativity in education. This global relevance is represented here by writings from authors from Brazil, Canada, China, Denmark, Italy, Israel, Japan, and Romania.